2020
DOI: 10.13057/biodiv/d220140
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Wildlife species used as traditional medicine by local people in Indonesia

Abstract: Abstract. Mardiastuti A, Masy'ud B, Ginoga LN, Sastranegara H, Sutopo. 2021. Short Communication: Wildlife species used as traditional medicine by local people in Indonesia. Biodiversitas 22: 329-337. Since a long time ago, wild animals (wildlife species) have been used by the local people as traditional medicine. Research has been conducted in some areas, but there was no study that incorporates all data. The objective of this research was to collect nation-wide information on the wildlife species (mammals, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 25 publications
0
19
0
2
Order By: Relevance
“…In rural contexts, people depend on wildmeat (or bushmeat) to ensure food security, generate income, or consume as a festival food in special events to perpetuate traditions and cultural identity (Lescuyer and Nasi 2016, van Vliet et al 2016, Alves and van Vliet 2018. Wildlife plays a key cultural role in certain societies, particularly for its use in traditional medicine (Mardiastuti et al 2021), arts and crafts (Jiao and Lee 2021), and for spiritual purposes (Boakye et al 2019). Wildlife products are also found in luxury markets across the world, often procured through illegal market chains; rhinoceros horns are used by Vietnamese businessmen as a signal of their social status (Truong et al 2016), and reptile skins are used in the fashion industry in the USA (Sosnowski and Petrossian 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In rural contexts, people depend on wildmeat (or bushmeat) to ensure food security, generate income, or consume as a festival food in special events to perpetuate traditions and cultural identity (Lescuyer and Nasi 2016, van Vliet et al 2016, Alves and van Vliet 2018. Wildlife plays a key cultural role in certain societies, particularly for its use in traditional medicine (Mardiastuti et al 2021), arts and crafts (Jiao and Lee 2021), and for spiritual purposes (Boakye et al 2019). Wildlife products are also found in luxury markets across the world, often procured through illegal market chains; rhinoceros horns are used by Vietnamese businessmen as a signal of their social status (Truong et al 2016), and reptile skins are used in the fashion industry in the USA (Sosnowski and Petrossian 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Food and medicine derived from wildlife have important nutritional values especially in times of crisis, although the wildlife food often regarded as supplementary to local peoples' diet [13]. Mardiastuti, et al [14] reported that the Javan porcupine (H. javanica) and the Malayan porcupine (H. brachyura) are used by local people in Indonesia as traditional medicine.…”
Section: Introductionmentioning
confidence: 99%
“…The meat from any terrestrial wild animals, or commonly called as bushmeat, is an alternate source of nutrients [1] and commonly consumed in several region in Indonesia as the main protein source and believed as a traditional remedy of several diseases [2]. More than 300 wildlife species varies from IOP Publishing doi:10.1088/1755-1315/1107/1/012127 2 amphibians to mammals were consumed for various purposes in Indonesia, in which 114 species were used for medicinal purposes [2]. One of animal that popularly exploited for consumption is Sunda porcupine (Hystrix javanica) [3] which is distributed from Java Island to Sumbawa [4] and has been exploited as bushmeat mostly in Central Java [3].…”
Section: Introductionmentioning
confidence: 99%
“…Sunda porcupine meat has a lower cholesterol content, compared to beef, lamb, pork, sambar deer dan Java deer [5]. Some of their body parts were consumed as traditional remedies for bezoar for anticancer medicine [2,6], meat for improving body vitality, while liver and bile salt for curing asthma and their quills were believed can be used to treat dental diseases [7,8]. Due to the threat of uncontrolled hunting [4], the porcupine is currently protected by Indonesian government under the Regulation of The Ministry of Environment and Forestry number P.106/MENLHK/SETJEN/KUM.1/12/2018.…”
Section: Introductionmentioning
confidence: 99%